lmplementation ofthe WНО Framework Convention on ТоЬассо Control in the Russian Federation: action points - N. F. Gerasimenko; R. G. Oganov; G. Ya. Maslennikova; I. E. Koltunov; A. M. Kalinina; S. A. Shalnova (Кардиоваскулярная терапия и профилактика)
.